Secondary infertility caused by a midline cyst of the prostate - T. Dewaele; L. D’Hooghe; K. Everaert; P. Devisschere (Journal of the Belgian Society of Radiology, 2014)
A 27-year-old male was referred to the urologist for evaluation of secondary infertility. Semen analysis by the referring physician showed a severe oligoasthenoteratozoospermia (OAT). The patient had no urinary symptoms or sexual complaints and the past medical history was unremarkable. Physical examination revealed thickened spermatic cords, suggesting a possible obstruction of the vasa deferens. A small varicocele was noticed on both sides. External genitalia and secondary sexual characteristics were otherwise normal. Hormonal laboratory findings were unremarkable. An MRI was performed to detect a possible obstructive cause of infertility. T2 weighted images (T2-WI) showed a sharply delineated, homogenous hyperintense cystic structure (c) of 2.5 × 2 cm dorsally at the midline in the prostate (P) (Fig. A). This cyst reached beyond the cranial and dorsal edge of the prostate (Fig. B). Furthermore, significantly swollen seminal vesicles (SV) and vasa deferens (VD) were noted (Fig. C, D). These findings suggested an obstruction of the ejaculatory ducts caused by the prostatic cyst, resulting in distension of the vasa deferens and seminal vesicles. This was considered the probable cause of secondary infertility in this patient. Subsequently, a transurethral unroofing of the cyst was proposed as an attempt to restore fertility. However, this treatment was refused by the patient.